THE ROLE OF FOLK ARTS AND CRAFTS OF DAGESTAN IN CONSOLIDATING AND EXPANDING THE TOURIST-EXCURSION ROUTES - G. G. Gazimagomedov (Юг России: экология, развитие, 2017)
Aim. The aim of this study is to create and represent the tourist routes in the places of the traditional folk arts and crafts in the Republic of Dagestan.Research Methodology. In the first stage of the study, according to the register and public materials we identified and studied traditional places of folk arts and crafts; carried out monitoring of existing tourist routes and programs. Developed routes are included in the tourist route map.Findings and discussion. We developed five radial exit routes from the city of Makhachkala, characteristics of which are presented below. Folk arts and crafts of Dagestan are a unique part of the artistic culture and at the same time, it is a branch of industry with a high level of tourist attractiveness. Today, Dagestan is one of the few areas in the modern world where traditional folk art is naturally a part of a contemporary social life having the rights of the dominant cultural unity due to the peculiarities of its historical development. Archaeological studies show that due to the geographical position, in Dagestan, there has been an interaction of significant aspects of cultural phenomena relating to the ancient civilizations of the Mediterranean, Western, Central and Eastern Europe, on the one hand, and the development of cultures of different regions of Asia, on the other hand. Coupled with the traditions of the ancient population of the Caucasus, they formed complex and varied artistic conglomerate.Conclusion. The study revealed the basic centers of traditional arts and crafts of the Republic of Dagestan, hiving a high tourism potential. On this basis, we developed five tourist-excursion routes. These routes are included in the information booklet, which has a marketing and information value.